Friends, Enemies, Firearms: American Gun Rights and the Economy of Racial Harm - Driscoll, Jennifer Anne (My University, 2023)
Who is the legitimate subject of gun rights? Throughout American history this question has been answered with racial exclusions both formal and informal. This dissertation tracks the development of the idea of gun rights as a marker of full citizenship, a status that has been racially demarcated since colonial times. In three case studies I show how the American gun debate is saturated with ideas of racial threat, and how gun rights have been deployed to manage an ever-evolving economy of racial harm. I begin by charting the origins of the economy of racial harm in the American colonies, in which Native Americans and Blacks, figured as racialized Others, loom dangerously over the body politic, threatening both its telos and its survival. In response, the American colonies and the American state sought to prevent racial harm to whites through robust gun rights for white Americans and firearm restrictions for non-whites. Next, I turn to a new era in the gun debate, in which gun control proponents in the 1960s, after losing the gun policy battle for most of the decade, advanced a new racial harm frame in which guns were a primary cause of Black oppression, as new data on gun violence in Black ghettos seemed to demonstrate. Although gun control advocates sought to transcend racial harm through rational government, gun control opponents, motivated by a desire to protect white sovereignty in the post-Civil Rights landscape, appropriated the language of racial harm to argue that gun control was the true cause of racial harm to Blacks. In place of gun control they pushed for harsher penalties for criminal gun use, a compromise that protected white gun rights at the expense of Black men’s freedom. Finally, I examine the propagation of the gun rights movement’s antiracist rhetorical frame from the 2010s to the present, which has become one of the most effective tools in the campaign to expand the right to carry firearms. This frame emphasizes Black Americans’ historical exclusion from gun rights and disparate vulnerability to violence in poor, racially segregated neighborhoods, a racial harm frame oriented around Black criminality as much as Black vulnerability. White gun advocates have propagated this antiracist rhetoric, promoting the notion that a multiracial coalition of gun owners is united against a common enemy, the (racialized) criminal. However, members of minority groups have seized ownership of the antiracist frame to defend their right to protect themselves, not from everyday crime, but from white supremacist violence. Thus, the antiracist frame has destabilized not only the white monopoly on gun rights, by expanding notions of who counts as a legitimate subject of gun rights, but also the white monopoly on gun rights rhetoric. Yet the broadening of mainstream gun rights subjecthood is predicated on adherence to traditionally white, male conceptions of individual sovereignty and legitimate violence, inflaming fantasies of white sovereignty at the continued cost of predominantly Black lives.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: firearms regulation; friend-enemy distinction; gun control; gun rights; racial harm; Political science; Political science